Pengaruh dukungan sosial atasan pada optimisme karyawan PT Propan Raya ICC Malang dalam bekerja di era new normal Covid-19 - Lusia Wahyu Septianingrum; Dellawaty Supraba (University of Merdeka Malang, 2021)
The COVID-19 pandemic that circulated in many areas in a wide geographical scope has initiated the new normal policy. These policies have an impact on employees. To survive, employees need high optimism. To generate optimism, encouragement is needed from within oneself and from others. This study aims to determine the effect of superior social support on the optimism of PT Propan Raya ICC Malang employees in working in the new normal era of covid-19. This study uses the variables of optimism and social support. The subjects of this study amounted to 48 individuals who are employees of PT Propan Raya ICC Malang. The sampling technique used is saturated sampling. This study uses a quantitative approach. The analytical method used is simple regression analysis. The results showed that there was a significant influence between superior's social support on optimism with a probability of 0.000 (p 0.05) so the hypothesis was accepted with a large effect of 65% (R square = 0.652).